Analytical solution for kinematic response of stepped pipe shafts in unsaturated soil under vertically incident P-waves - Jiale Yang; Honggui Di; M. Hesham El Naggar; Long Chen; Xiaohui Zhang; Chao He; Shunhua Zhou (Soil Dynamics and Earthquake Engineering, 2026)

A comprehensive survey of data-driven technologies for construction solid waste recycling systems - Fangyu Li; Mohan Niu; Honggui Han; Nan Zhang (Waste Management, 2026)

Kinematic response of floating pipe piles in unsaturated poro-viscoelastic medium subjected to vertically propagating P-waves - Honggui Di; Jiale Yang; Chao He; Xiaohui Zhang; Shunhua Zhou (Ocean Engineering, 2026)

Mechanism of deep and selective sulfate removal from high-concentration CaCl2 solutions via porous interfacial deposition on calcium-modified carbon - Ghulam Mustafa; Zhe Zhang; Honggui Liu; Zhen Chen; Zihong Cheng; Cheng Yang; Shuqin Liu; Feilong Liang; Yong Guo; Guodong Wan; Niyazi Abulaizi; Wei Ma (Journal of Cleaner Production, 2026)

Early maternal separation induced spatial memory deficits through hippocampal inflammation in piglets - Qi Han; Baochen Xie; Yuxi Shen; Ting Wei; Wenhui Zhang; YongJian Cui; Honggui Liu; Shuai Liu (Applied Animal Behaviour Science, 2026)

Chlorination level-dependent amplification of antibiotic resistance genes dissemination by chlorinated paraffins via ROS-mediated natural transformation - Honggui Wang; Qi Dai; Yanhui Yin; Linjie Wang; Chenxi Li; Qingqing Sheng; Zhe Piao; Ya Zhang (Journal of Hazardous Materials, 2025)

Kinematic response of double-lined shafts embedded in homogeneous unsaturated soil subjected to P-wave excitation - Jiale Yang; Honggui Di; Shunhua Zhou; Guangbei Su; Chao He; Xiaohui Zhang (Soil Dynamics and Earthquake Engineering, 2025)

The group-modified nanoplastics bring higher risk on promoting the antibiotic resistance genes dissemination by stimulate bacteria to generate more ROS under aerobic condition - Chenxi Li; Yang Liu; Linjie Wang; Qi Dai; Zhe Piao; Ya Zhang; Honggui Wang (Journal of Environmental Chemical Engineering, 2025)

Chiral pesticide permethrin promotes the antibiotic resistance genes dissemination by transformation: Different chiral isomers engage in distinct regulatory pathways - Chenxi Li; Linjie Wang; Qi Dai; Yang Chong; Satoshi Utsunomiya; Honggui Wang; Ya Zhang; Jie Han (Journal of Hazardous Materials, 2025)

Identification of the sex-linked region of Siniperca scherzeri and development of sex-specific markers - Yang Li; Yu Cui; Xiaojun Ye; Maoyuan Wang; Hao Xu; Yannian Wu; Jian Jin; Honggui Huang; Mingyong Lai; Zhiyong Wang; Dongling Zhang (Aquaculture, 2025)

Nanoplastics facilitate the spread of antibiotic resistance genes in chemically induced competent bacteria: The hydrogen peroxide plays as the main signal factor - Chenxi Li; Qian Zhang; Linjie Wang; Zhe Piao; Ya Zhang; Yang Chong; Xin’an Jiao; Honggui Wang (Journal of Environmental Chemical Engineering, 2025)

A rapid method for measuring the rock brittleness index: Rapid characterization of rock brittleness based on LIBS technology - Qinghe Zhang; Weiguo Li; Liang Yuan; Chao Liang; Honggui Pan (Tunnelling and Underground Space Technology, 2024)

Deformation analysis and protection measures of existing metro tunnels effected by river channel excavation in soft soils - Chao He; Yinghao Cai; Chenqiang Pu; Shunhua Zhou; Honggui Di; Xiaohui Zhang (Tunnelling and Underground Space Technology, 2024)

Identification of Increased Grain Length 1 (IGL1), a novel gene encoded by a major QTL for modulating grain length in rice - Jiayu Niu; Fei Wang; Chengcheng Yang; Qiwen Ye; Jingxian Huang; Yumei La; Qianqian Wang; Jie Dai; Tiange Hu; Liran Sang; Peijiang Zhang; Yu Zou; et al. (Theoretical and Applied Genetics, 2024)

The fate and supply capacity of potassium in biochar used in agriculture - Liqun Xiu; Wenqi Gu; Yuanyuan Sun; Di Wu; Yuning Wang; Honggui Zhang; Weiming Zhang; Wenfu Chen (Science of The Total Environment, 2023)

Semi–analytical solution for ultimate bearing capacity of straight–jointed segmental tunnel lining - Zhang Xiaohui; Zhou Shunhua; Di Honggui; Wang Peixin; Wang Jingtong (Tunnelling and Underground Space Technology, 2023)

Complete nitrogen removal from low-strength wastewater via double nitrite shunt coupling anammox and endogenous nitrate respiration: Functional metabolism and electron transport - Qiongpeng Dan; Rui Du; Tong Wang; Tiantian Sun; Honggui Han; Xiaorong Zhu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

An analytical model for evaluating the dynamic response of a tunnel embedded in layered foundation soil with different saturations - Honggui Di; Huiji Guo; Shunhua Zhou; Binglong Wang; Chao He; Xiaohui Zhang (Earthquake Engineering and Engineering Vibration, 2022)

Selenium Deficiency Induces Inflammation via the iNOS/NF-κB Pathway in the Brain of Pigs - Yilei Zhang; Jiawen Cui; Yingfei Lu; Chunzheng Huang; Honggui Liu; Shiwen Xu (Biological Trace Element Research, 2020)

Chlorpyrifos induces redox imbalance‐dependent inflammation in common carp lymphocyte through dysfunction of T‐cell receptor γ - Jie Yang; Yafan Gong; Jingzeng Cai; Yingying Zheng; Honggui Liu; Ziwei Zhang (Journal of Fish Diseases, 2020)
Chlorpyrifos is a poisonous pesticide that is highly toxic to fish and aquatic organisms. However, there are fewer reports about how chlorpyrifos influences the redox balance of immune cells. Herein, the head kidney tissue treated with chlorpyrifos to do transcriptome analysis and TCR γ was screened out. Subsequently, we established TCR γ knockdown and overexpression carp head kidney lymphocyte models, respectively, by using RNA interference and pcDNA3.1. Real‐time PCR, fluorescent staining, oxidation and antioxidant kit were used to detect the related factors. We found that TCR γ knockdown significantly increased the mRNA expression of HSP70 and HSP90 and decreased the mRNA expression of SOD and CAT. Meanwhile, TCR γ knockdown reduced the activities of GSH, GSG‐PX, T‐AOC, CAT and SOD and increased the content of MDA and H 2 O 2 and activities of iNOS. Adverse results were obtained in TCR γ overexpression group. Additionally, TCR γ knockdown significantly increased the mRNA expression of IFN‐γ, IL‐1β, IL‐8, IL‐10, Nrf2 and NF‐κB, but relieved TCR γ overexpression, in which the process of inflammation was activated. Our results reported here indicated that chlorpyrifos induces redox imbalance‐dependent inflammation in common carp lymphocyte through dysfunction of T‐cell receptor γ, and HSPs play potential protective role in entire process.

Characterization and fine mapping of Arabidopsis RLL3, a locus required for DNA demethylation pathway - Wei Miao; Jie Dai; Yumei La; Chong Lu; Jianzhen Zhang; Xinyue Hong; Shaoxia Zhou; Qianqian Wang; Xiangyu Wang; Qi Rui; Feng Tan; Honggui La (Molecular Genetics and Genomics, 2020)

Mathematical Modeling of Slurry Infiltration and Particle Dispersion in Saturated Sand - Shunhua Zhou; Xiaohui Zhang; Di Wu; Honggui Di (Transport in Porous Media, 2018)